Acute Diarrheal Diseases Among Preschool Children in Western Maharashtra, India - Tondare, Mahesh B; Raje, Vaishali V; Kakade, Satish V; Rayate, Madhavi V (National Journal of Community Medicine, 2014)
Background: Malnutrition and infectious diseases both occur in the same unfortunate children and together they play a major role in causing the high morbidity and mortality in them. Acute Diarrhoeal diseases (ADD’s) are reported to be the 2nd leading cause of child morbidity and mortality. Objectives: To study the attack rate of Acute Diarrhoeal Disease among pre-school children and to study the socio-demographic variables of pre-school children suffering from Acute Diarrhoeal Disease. Methods: A Longitudinal study was conducted among preschool children (3-5years) of Private pre-primary school of urban area and followed for the period of one year. Mother/ guardian/ teacher was interviewed by using pre-tested proforma. Results: About 56% of children found suffering from ADD with 0.6 episodes per children per year among private pre-primary school. Higher proportions of ADD affected children were residing in nuclear type of family, belonging to middle socio-economic class, mothers were literate & housewives, born with order >2 compared to non ADD affected children. Conclusion: More than half of children from private pre-primary schools suffered with nearly one attack of Acute Diarrhoeal Disease. Maternal illiteracy and working mothers found favorable factors. Immunization coverage, EBF and proper weaning play a very important role in prevention of infections.